Nurcholish Majid's Inclusive Interpretation Pattern in Understanding Religious Tolerance Verses - Ghozali, Abdul Malik; Masruchin, Masruchin; Fauzan, Fauzan (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
Inclusive theology manifests itself in religious plurality, particularly in Indonesia, a pluralistic country with many diverse races, ethnicities, and religions. Islam, through its holy text Al-Qur'an, instructs its people to appreciate one another and forbids religious disputes. This paper attempts to reinterpret the verses of religious tolerance by combining the theme interpretation method and content analysis with an inclusive theological approach to address the challenge of interpreting the verses of tolerance. This paper leads to an understanding that a pluralist mindset is required in building inter-religious interactions in Indonesia by embracing the reality of other religions while maintaining one's Muslim identity.